Northwest History. Alaska, Glaciers. United States. (1937)
Alaskan Glaciers Shrinking In Size. ALASKAN GLACIERS SHRINKING IN SIZE. FAIRBANKS, Alaska, March 5 (AP)—Glaciers on a 250-mile-long mountain range between Fairbanks and the Gulf of Alaska have undergone a tremendous shrinkage in the past three years, Airplane Pilot Harold Gillam, who has been flying over the area for years, said today. Many smaller glaciers have disappeared, while larger ones have shrunk from both ends. In contrast is the Black Rapids glacier, which continues to move toward the Richardson highway 125 miles south of here. "The entire region looks entirely different than it did three years ago," Gillam said, adding he could not explain the cause of,the glacial recession. Alaska airlines pilots reported the Black Rapids glacier has cut deep gashes into the sides of its valley. They estimated its vertical fall at more than 6000 feet since it began moving forward after fall rains.